Verbal memory and executive components of recall in adolescent binge drinkers - Porras Truque, Claudia; García Moreno, Luis Miguel; Gordo, Patricia Mateos; Ordoñez, Xavier G.; Cadaveira, Fernando; Corral, Montserrat (Frontiers in Psychology, 2023)
Binge drinking (BD) is a common health-risk behavior among young people. Due to the incomplete maturation of the adolescent brain, BD can lead to structural and functional changes that impact neurocognitive processes, particularly executive functioning and verbal memory. This study aimed to investigate the influence of executive components, such as mnemonic strategies and error avoidance, on performance in a verbal memory test and the potential effects of BD on this performance. A sample of 160 college students (51.55% female) with a mean age of 18.12 ±0.32 years completed assessments for alcohol use disorders using the Alcohol Use Disorder Identification Test (AUDIT), as well as psychopathological (Symptom Checklist-90-R) and neuropsychological evaluations (Verbal Learning Test Spain-Complutense and WMS-III Logical Memory). The Intensive Drinking Evaluation Instrument (IECI) was utilized to gather detailed information about binge drinking habits, including the calculation of the highest blood alcohol concentration (BAC) during an episode of intake. Correlation and clustering analyses revealed a negative association between BAC values and verbal memory performance, as well as the use of memory strategies. The high BAC group (BD) exhibited negative values in verbal memory variables, higher accuracy errors, and less efficient strategy usage, while the low BAC group (No BD) demonstrated better memory test performance, fewer precision errors, and superior use of memory strategies. These findings support the hypothesis that, when solving tests requiring verbal memory, adolescents reporting a BD consumption pattern show fewer executive skills in their resolution and, therefore, achieved poorer performance than non-binge drinkers. Addressing excessive alcohol consumption in young individuals is crucial for safeguarding their cognitive development and overall well-being.